Democracy And Diversity: Political Engineering in The Asia - Pacific - REILLY, Benjamin (Oxford University Press, 2007)
This book explains how the Asia-Pacific's political reformers responded to the twin challenges of democracy and diversity through ambitious and often innovative political engineering. Far-reaching reforms to electoral, parliamentary, and party systems have seen the emergence of a distinctive regional model of democracy.